Digital Content Design for Promoting Open Trip: A Study of Effective Digital Marketing Communication Strategies in the Tourism Sector - Marellyda, Khairunissa Hany; Wihardi, Doddy; Jati, Rocky Prasetyo (Transpublika Publisher, 2025)
The rapid development of information technology and social media has significantly influenced the tourism sector, encouraging the adoption of digital marketing to enhance destination attractiveness. This study examines the implementation of digital content design to promote open trips in Sumberjaya Village, Sumur District, Pandeglang Regency, Banten, an area with strong natural tourism potential that remains underexposed. The research emphasizes the development of engaging social media content, community training in content creation, and the impact of digital promotion on tourist interest. The findings indicate that well-designed digital content significantly increases destination visibility, particularly among millennials and Gen Z. Social media platforms such as Instagram, TikTok, and Facebook play an important role in reaching these digitally oriented travelers, with Instagram selected as the primary promotional medium due to its visual and interactive features. Using a Participatory Action Research (PAR) approach, this study actively involved the local community, especially the Tourism Awareness Group (POKDARWIS), in digital content production and promotional activities. This participation not only enhanced Sumberjaya Village’s online presence but also strengthened community ownership in tourism development. In addition, the Open Trip model, allowing individuals to join tour packages without forming groups, proved effective in attracting young tourists seeking affordable, social, and authentic travel experiences. Overall, the integration of digital marketing, community-based tourism, and the Open Trip concept has positively contributed to sustainable tourism development in Sumberjaya Village by increasing destination visibility, generating local income, and strengthening community involvement in tourism management.